METHODS OF ANALYSIS AND ASSESSMENT OF THE ECONOMIC EFFICIENCY OF THE RAILWAY TRANSPORT SYSTEM (Marketing Journal, 2025)
This article examines the methods and indicators used to evaluate the economic efficiency of the transport system, particularly the railway sector. It analyzes global practices and contextualizes them within Uzbekistan’s transport development. A comprehens ive system of indicators based on flow process analysis and both static and dynamic efficiency perspectives is proposed. The study develops a systematic methodology for assessing transport strategy performance, infrastructure development, profitability, an d service quality. 153
Keywords: railway transport; economic efficiency; evaluation methods; logistics; flow processes; profitability; transport strategy; infrastructure; static and dynamic efficiency